Comparison of Outcomes After Partial Versus Complete Mesh Excision. Issue 1 (July 2020) - Kao, Angela M.; Arnold, Michael R.; Otero, Javier; Huang, Li-Ching; Prasad, Tanushree; Lincourt, Amy E.; Augenstein, Vedra A.
Abstract : Objective: Evaluate outcomes of patients undergoing mesh explantation following partial mesh excision (PME) and complete mesh excision (CME). Background: Ventral hernia repair (VHR) with mesh remains one of the most commonly performed procedures worldwide. Management of previously placed mesh during reexploration remains unclear. Studies describing PME as a feasible alternative have been limited. Methods: The AHSQC registry was queried for VHR patients who underwent mesh excision. Variables used for propensity-matching included age, BMI, race, diabetes, COPD, OR time>2 hours, immunosuppressants, smoking, active infection, ASA class, elective case, wound classification, and history of abdominal wall infection. Results: A total of 1904 VHR patients underwent excision of prior mesh. After propensity matching, complications were significantly higher (35% vs 29%, P = 0.01) after PME, including SSI/SSO, SSOPI, and reoperation. No differences were observed in patients with clean wounds, however in clean-contaminated, PME more frequently resulted in SSOPI (24% vs 9%, P = 0.02). In mesh infection/fistulas, higher rates of SSOPI (46% vs 24%, P = 0.04) and reoperation (21% vs 6%, P = 0.03) were seen after PME. Odds-ratio analysis showed increased likelihood of SSOPI (OR 1.5, 95% CI 1.05–2.14; P = 0.023) and reoperation (OR 2.2, 95% CI 1.13–4.10; P = 0.015) with PME. Conclusions: With over 350, 000 VHR performed annually and increasing mesh use, guidelines for management of mesh during reexploration are needed. This analysis of a multicenter hernia database demonstrates significantly increased postoperative complications in PME patients with clean-contaminated wounds and mesh infections/fistulas, however showed similar outcomes in those with clean wounds.